Sonic Interventions: Understanding and Extending the Domestic Soundscape - Oleksik, Gerard; Frohlich, David; Brown, Lorna M.; Sellen, Abigail (Proceedings of CHI 2008, 2008)
This paper presents a new study of the role, importance and meaning of sound in the home. Drawing on interview data and sound recordings gathered from seven households, this study offers fresh insight into the ways in which the domestic soundscape is managed and understood. The data revealed that household members engaged in a wide variety of sound management practices to monitor and control the real-time flow of sonic information throughout the home. They also showed that families were sometimes surprised and delighted by the ability to record fragments of the soundscape for later use. These findings suggest a number of roles for technology in enhancing the domestic soundscape and its associated behaviors, which we present here in the form of example sonic interventions created in a design workshop at the end of the project.